The use of ICT in public and private institutions of higher learning, Malaysia - Muhamat Dawam, Siti Rafidah; Ahmad, Khairul Adilah; Jusoff, Kamaruzaman; Tajuddian, Taniza; Elias, Shamsul Jamel; Wan Mansor, Suhardi (2009)
This study examines the extent of ICT utilization among the members of Faculty A of four public higher learning institutions (IPTA) and seven private higher learning institutions (IPTS) in Northern Malaysia. Its focus is on a) to investigate the extent of ICT resources provided by universities authorities, b) focus on types and extent of ICT usage in daily activities, c) to explore the ICT proficiencies level and d) to investigate the level of ICT integration in teaching activities. A total of 76 responses out of 77 from IPTA and only 105 out of 108 responses of IPTS are usable for further analysis in this study. Findings indicate that in the IPTA, though the facilities provided are not as plenty as in IPTS, the level of usage is quite encouraging. While in the IPTS, the levels of ICT usage among the educators are still not satisfactorily. Results also indicated that usage frequencies are more prone on informative in nature, besides integrating computer technology. Furthermore, the study also indicates that there were considerable differences in the use of ICT by educators in their perceived proficiencies and integrating computer technology. This study could be improved by expanding the total sampling population to all faculties in both universities. Methods of analysis could also be varied beyond the descriptive analysis done. Factors that could hinder the level of ICT usage by the educators could also be studied.